2001
DOI: 10.1029/1999jc000156
|View full text |Cite
|
Sign up to set email alerts
|

Validation of two algorithms to retrieve ocean wave spectra from ERS synthetic aperture radar

Abstract: Abstract. Wave spectra that are retrieved from ERS-1/2 synthetic aperture radar (SAR) wave mode observations with two different algorithms are validated against 6 years of buoy observations. The Max-Planck Institut fiir Meteorologie (MPIM) algorithm, which runs operationally at the European Centre for Medium-Range Weather Forecasts (ECMWF), is found to deteriorate the quality of the WAM spectrum which is used as a first guess. The Semi-Parametric Retrieval Algorithm (SPRA) does not use a first-guess spectrum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…In accordance to the results presented by Dunlap et al (1998), the mean value of SWH retrieved using the MPI algorithm is about 10% higher than the mean value of SWH computed by the WAM. However, in disagreement with Voorrips et al (2001), the performance of the MPI scheme is shown to be as good as (or in some frequency bands even somewhat better) than the wave model for values of SWH computed considering only the low wavenumber part of the spectrum directly measured by SAR -waves longer than 225 m.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In accordance to the results presented by Dunlap et al (1998), the mean value of SWH retrieved using the MPI algorithm is about 10% higher than the mean value of SWH computed by the WAM. However, in disagreement with Voorrips et al (2001), the performance of the MPI scheme is shown to be as good as (or in some frequency bands even somewhat better) than the wave model for values of SWH computed considering only the low wavenumber part of the spectrum directly measured by SAR -waves longer than 225 m.…”
Section: Discussionmentioning
confidence: 87%
“…Heimbach et al (1998) comparing WAM estimates against SAR retrievals that used the wave model results themself as fi rst guess have found a systematic underprediction of the energy of the swell components and an overprediction of the wind sea, whereas from measurements presented in this work this trend was not observed with the model being virtually bias free over the whole spectral range. Confi rming the fi ndings of Voorrips et al (2001), the MPI scheme in fact deteriorates the values of SWH used as fi rst guess for the inversion adding its own error with the scatter in the WAM-Buoy comparisons being 25% lower than the SAR-Buoy scatter. In accordance to the results presented by Dunlap et al (1998), the mean value of SWH retrieved using the MPI algorithm is about 10% higher than the mean value of SWH computed by the WAM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the overall agreement was quite promising it was clear that an assessment against independent data, such as spectra from a directional buoy, would be more likely to point to any deficiencies of the method. More recently Voorrips et al (2001) compared the MPI and the SPRA schemes against several non-directional buoys deployed mostly off the North American coast. In this work it became clear that both schemes show room for improvement, and that their main deficiencies lie in how to augment the spectral information beyond the azimuthal cutoff.…”
Section: Introductionmentioning
confidence: 99%
“…The main problem for such a comparison is a lack of available directional buoy data in deep water. The few directional buoys available to Voorrips et al (2001) were not included in their analysis because they are moored in relatively shallow coastal waters, where one would expect a greater spatial variation of the wave parameters when compared to the more spatially homogeneous situations in the open sea.…”
Section: Introductionmentioning
confidence: 99%